Selection of Trichoderma spp. strains for the control of Sclerotinia sclerotiorum in soybean - Haddad, Patrícia Elias; Leite, Luiz Garrigós; Lucon, Cleusa Maria Mantovanello; Harakava, Ricardo (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate, in vitro and in vivo, the potential of Trichoderma spp. strains to control Sclerotinia sclerotiorum in soybeans (Glycine max) and to perform the molecular identification of the best performing strains. The effect of 120 strains of Trichoderma spp. on the viability of S. sclerotiorum sclerotia was evaluated in vitro through immersion in suspension of conidia from the antagonists and plating in culture medium. The best performing strains were evaluated in vivo, in a greenhouse, for control of the pathogen inoculated on 'Pintado' soybean seeds and plants. Of the 120 strains tested in vitro, 22 strains of Trichoderma spp. caused 100% inhibition of sclerotia germination. In the greenhouse, five strains inhibited the negative effect of the pathogen on seed germination and two strains increased in up to 67% plant dry matter. The best performing strains were identified as T. koningiopsis (3 strains), T. asperelloides (3), T. atroviride (2), and T. virens (1). Trichoderma strains are able to protect soybean plants from the harmful effect of S. sclerotiorum and, at the same time, they can promote the growth of the aerial part in greenhouse conditions.